EFEKTIFITAS PORTAL AKADEMIK SEBAGAI SARANA PENYAMPAIAN INFORMASI AKADEMIK BAGI MAHASISWA UNIVERSITAS RIAU - Monica Restama; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
University of Riau in practice has a goal of learning is Three Dharma University. So as to manage the information that is extremely diverse academic university, the University of Riau using academic portal. However, in reality Riau University academic portal system can not ensure smooth in the delivery of academic information that can be enjoyed by the students. So the purpose of this first study, to determine the effectiveness of academic information as a means of delivering information to students. Second, to find out why the service is in the navigation can not be entirely accessible. Third, to determine the constraints of Riau University computer center to provide information updates.This research uses descriptive qualitative method. Students research subject is the University of Riau, Riau University Computer Center employees and Agency Services Faculty of Information and Communication Technology, using purposive sampling technique.The technique of collecting data through participant observation, in-depth interviews and documentation.The results show first, academic portal as a means of delivering academic information is strongly influenced by 3rd parties, namely the performance of the computer room, computer center and the University of Riau quality ISP (Internet Service Provider) have not been effective. Second, academic portal navigation facilities can not be entirely inaccessible due to lack of supervision of Riau University computer center employees. Third, the lack of the number of servers, expertise and supervision of the computer center staff and network intrusions from the Internet Service Provider is a barrier in providing information that is updated.Key word : Effectiveness, Academic Portal, Information Systems,Academic Information System.